Evaluation of the Educational Management Program in Light of the Academic Accreditation Standards from the Point of View of the Faculty Staff Members of the Jordanian Universities in Irbid - Dhiab Al-Azmi, Issa Falah (Technium Education and Humanities, 2021)
The study aimed to determine the degree of the evaluation of the educational management program in light of the academic accreditation standards from the point of view of the faculty staff members of the Jordanian universities in Irbid. The researchers adopted the descriptive, analytical approach and the study sample consisted of (17) faculty staff members specialized in educational management who were selected through the complete consensus due to the limited size of the study population. The results of the study depended on a questionnaire consisting of (4) fields requiring the viewpoints of the participants for evaluating the educational management program. The results of the study indicated that the degree of the evaluation of the educational management program in light of the academic accreditation standards at the Jordanian universities in Irbid from the point of view of the faculty staff members was medium by a mean of (3.47) and a standard deviation of (0.46) and that there were no statistically significant differences in the estimates of the faculty staff members for the degree of the evaluation of the educational management program in light of the academic accreditation standards attributed to the variables of (gender, academic rank, and career experience). One of the most prominent recommendations is working on improving the educational management program in light of the academic accreditation standards in terms of the content and objectives of this program, the study plan, teaching methods and research services and facilities.